2018
DOI: 10.1111/all.13485
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and long‐term gut microbiota variation in allergic disease: A prospective study from infancy to school age

Abstract: We identified both temporal and long-term variation in the differential abundance of specific bacterial genera in children developing IgE-associated allergic disease. Improved dietary interventions aiming at expanding immune-modulatory taxa could be studied for prevention of allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…Prevotella is difficult to culture, being a strict anaerobe, and its carriage was not reported. However, a recent longitudinal analysis of 63 Swiss children found, using culture-independent techniques, underrepresentation of the genus Prevotella in fecal samples collected at 6 months, 13 months and 8 years from participants with IgE related allergic disease 22 . Consistent with this, a study of 83 South African children found a cross-sectional association between low relative abundance of P. copri and atopic dermatitis 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella is difficult to culture, being a strict anaerobe, and its carriage was not reported. However, a recent longitudinal analysis of 63 Swiss children found, using culture-independent techniques, underrepresentation of the genus Prevotella in fecal samples collected at 6 months, 13 months and 8 years from participants with IgE related allergic disease 22 . Consistent with this, a study of 83 South African children found a cross-sectional association between low relative abundance of P. copri and atopic dermatitis 23 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Animal studies have provided compelling evidence to support a causal role of the intestinal microbiota and its metabolites, especially in early life, in the etiology of allergic diseases. [3][4][5][6] Numerous epidemiological studies [7][8][9][10][11][12] also suggest that the infant intestinal microbiota plays an important role in the manifestation of allergic diseases and asthma, although actual results vary considerably between studies. Approximately half of the studies that examined intestinal microbial diversity in infancy and childhood reported a lower diversity among children with (subsequent) allergies, whereas the remaining studies found no evidence for such an association.…”
mentioning
confidence: 99%
“…An increased microbial diversity along with the relative abundance of certain bacteria, such as Lactobacillus spp. (63), has been correlated with a lower risk of IgE-associated allergic diseases, namely atopic dermatitis and wheezing, through a decreasing Th2-mediated response (64). No significant association between the diversity of complementary foods and allergic rhinitis has been found so far (65).…”
Section: Early Lifementioning
confidence: 99%